2020
DOI: 10.1021/acsnano.0c00659
|View full text |Cite
|
Sign up to set email alerts
|

Single Vanadium Atoms Anchored on Graphitic Carbon Nitride as a High-Performance Catalyst for Non-oxidative Propane Dehydrogenation

Abstract: In comparison with oil-based cracking technologies, the on-purpose dehydrogenation of propane (PDH) is a more eco-friendly and profitable approach to produce propylene. By means of density functional theory calculations, the present work reveals that the single vanadium (V) atom anchored on graphitic carbon nitride (V1/g-C3N4) may serve as a promising single-atom catalyst for non-oxidative PDH with industrially practical activity, selectivity, and thermal stability. The high activity of V1/g-C3N4 for PDH is at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 58 publications
(108 reference statements)
4
58
0
Order By: Relevance
“…The fast and efficient redox cycles of Cr 3+ / Cr 2+ further promote the electron transfer and the exposure of more Cr(II)-N 4 reactive sites for H 2 O 2 activation in the HFLR. Moreover, this metalloporphyrin-like Cr-N 4 sites are very stable, which leads to an unprecedented wide working pH range (3)(4)(5)(6)(7)(8)(9)(10)(11) and remarkable durability and reusability of the SA-Cr/ PN-g-C 3 N 4 for HFLR. Also, this coupled system will minimize the consumption of H 2 O 2 and metallic catalysts due to the production of extra reactive species by photocatalysis and the utmost utilization of metallic catalytic sites of the SACs.…”
Section: Mechanism Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The fast and efficient redox cycles of Cr 3+ / Cr 2+ further promote the electron transfer and the exposure of more Cr(II)-N 4 reactive sites for H 2 O 2 activation in the HFLR. Moreover, this metalloporphyrin-like Cr-N 4 sites are very stable, which leads to an unprecedented wide working pH range (3)(4)(5)(6)(7)(8)(9)(10)(11) and remarkable durability and reusability of the SA-Cr/ PN-g-C 3 N 4 for HFLR. Also, this coupled system will minimize the consumption of H 2 O 2 and metallic catalysts due to the production of extra reactive species by photocatalysis and the utmost utilization of metallic catalytic sites of the SACs.…”
Section: Mechanism Studiesmentioning
confidence: 99%
“…Single‐atom catalysts (SACs) bridge the gap between homogeneous catalysis and heterogeneous catalysis and maximize the atomic utilization efficiency of transition and noble metals. [ 1,2 ] SACs on support surfaces possess unique chemical and physical properties, fine‐tuned active sites, and outstanding activity, selectivity and durability, [ 3–5 ] which are different from the conventional catalysts from sub‐nanoscale to microscale. However, with the decrease of particle size, metal catalysts tend to self‐aggregate into clusters or particles because of the dramatically increased surface energy.…”
Section: Introductionmentioning
confidence: 99%
“…DFT calculation can be conducted by different level of theory, and B3LYP/6‐31G level is the effective method to predicate the properties of small nonmetals such as oxygen and metals such as vanadium. [ 40–44 ] The input files of each vanadium–oxygen species for the DFT calculation are shown in Supporting Information.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…[197] Kong et al theoretically confirmed that vanadium atoms were anchored on graphitic carbon nitride for nonoxidative propane dehydrogenation. [346] The high activity of V 1 /g-C 3 N 4 was attributed to low coordination 3d orbital of V atoms, while propylene selectivity was initiated from inhibition of di-σ binding mode of propylene on single V atoms.…”
Section: Organic Transformationsmentioning
confidence: 99%